Effect of plasmon resonance of metal nanoparticles on spectral-luminescent properties of polymethine dye - N.Kh. Ibrayev; E.V. Seliverstova; N.D. Zhumabay; G.S. Omarova; A.A. Ishchenko (Қарағанды университетінің хабаршысы. Физика сериясы)
Spectral-luminescent properties of polymethine dye in ethanol solution were studied upon the addition of gold and silver nanoparticles. The absorption spectrum of Au nanoparticles has a large degree of overlap with the absorption and fluorescence spectra of the dye than the absorption spectrum of Ag. In the presence of plasmon nanoparticles, both the absorption and fluorescence of the polymethine dye was increased. The position of the maxima of the absorption and the fluorescence bands of the dye and their half-width were not changed. The growth of fluorescence in 4 times was recorded for the concentration of Ag nanoparticles, equal to 3*10-14 mol/l, and for the concentration of Au nanoparticles, equal to 7*10-11 mol/l. The greatest increase in the fluorescence intensity of polymethine was registered for solutions with gold nanoparticles. The enhancement of the fluorescence of the dye and the decrease in its lifetime can be connected with an increase in the rate of electronic transitions in dye molecules that are located in the near field of metallic nanoparticles with excited plasmons. The decrease in the intensity of the luminescence of the dye at high concentrations of nanoparticles can be the result of nonradiative energy transfer from polymethine molecules to metal particles, which leads to a decrease in the probability of radiative decay of excited molecules.